Alcohol and drugs use and solutions to its restricting in the opinions of Szczecin’s Junior High School pupils - Musiał, Barbara; Czaja-Bulsa, Grażyna; Szechter-Grycewicz, Aneta; Brodzińska, Beata; Marasz, Agata (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Adolescents’ alcohol and drugs use has negative impact on their health and is a big civilization threat. Aim of study. Paper’s purpose is to define situations promoting alcohol and drugs use among young people as well as places where those substances are consumed and solutions to reducing those behavior which were considered important. Material and methods. Survey questionnaire was used as a research method. There were 918 respondents, 58% girls and 42% boys in the age bracket of 13–16 from five Szczecin’s Junior High Schools. Results were analyzed statistically. Results. Adolescents drink alcohol most often during meeting with same-age people (76%), during family holidays and events (53%), because of successes in school (50%), but also without any occassion (48%). Drugs on the other hand are most commonly used during sport events (58%), in the moment of hopelessness (40%) or without an occassion (35%). Most affective way of reducing the phenomena of addiction according to adolescents is help of same-age people and expelling abusers from schools. In the case of addiction Junior High Pupils expect help foremostly from their parents. Conclusions. Alcohol drinking and drugs use among adolescents is a serious problem, deeply associated with their functioning in a social group (family, same-age people). Acceptation of alcohol drinking in the family lowers essentially the chance of reducing this behavior among adolescents.